Aqueous and ethanolic extracts of welsh onion, Allium fistulosum, attenuate high-fat diet-induced obesity - Yoon-Young Sung; Dong-Seon Kim; Seung-Hyung Kim; Ho Kyoung Kim (BMC, 2018)
Abstract Background Allium fistulosum (Welsh onion) is a traditional medicinal plant used for the treatment of colds, influenza, abdominal pain, headache, and heart disease. This study evaluated the effects of A. fistulosum ethanolic extract (AFE) and aqueous extract (AFW) on body weight and other obesity-related parameters. Methods Male 8-week-old C57BL/6 J mice were fed either a standard chow diet (normal control) or a high-fat diet (HFD) either alone (HFD-control) or in combination with G. cambogia extract containing hydroxycitric acid (HCA, an herbal weight-loss supplement), conjugated linoleic acid (CLA, a weight-loss supplement), orlistat (a clinically available anti-obesity drug), AFW, or AFE (n = 6 mice per group) for 6 weeks. At the end of 6 weeks, several body weight and obesity-related parameters were examined, including: liver and adipose weight, adipocyte size, serum lipid profiles, liver expression of adenosine monophosphate-activated protein kinase (AMPK), and adipose tissue expression of uncoupling protein 2 (UCP2). Results High-performance liquid chromatography showed that both AFE and AFW contain ferulic acid and quercetin. Oral administration of AFW and AFE to HFD-fed mice decreased body weight as well as liver and adipose tissue weight and adipocyte size. Serum lipid profiles and adiponectin levels were improved in HFD-fed mice treated with AFE but not AFW. However, both AFW and AFE significantly attenuated HFD-induced changes in serum leptin and insulin-like growth factor 1 levels, liver expression of AMPK, and adipose tissue expression of UCP2. Conclusions The findings from this study suggest that A. fistulosum extracts have potential as functional food materials for weight control in obesity.